The Empowerment of PKK Members in RW 5 Lidah Wetan, Surabaya through the Development of Gulijat-Based Products - Fera Ratyaningrum; Siti Mutmainah; Agung Ari Subagio; Aqim Amral Hukmi; Kartika Herlina Candraning Shiam (Elevasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2025)
This community service activity aims to empower the women of PKK RW 5 Lidah Wetan, Surabaya, through training in the jumputan fabric dyeing technique based on the Gulijat method. This program is carried out in collaboration between the Fine Arts Education Study Program and the PKK RW 5 organization to enhance members' skills in creating high-economic-value textile products. The training is conducted in several stages, including technique introduction, demonstrations, and hands-on practice using specialized materials and equipment such as napthol, caustic soda, and napthol salt. The results of this training include textile products such as fabrics, headscarves, and tote bags with unique designs that participants can develop into independent businesses. The evaluation shows that participants not only understand this dyeing technique but are also motivated to further develop it. This program is expected to support family economic improvement and strengthen the independence of PKK women in creating creative business opportunities in the textile sector.